Pendampingan Drafting Pengajuan Hak Kekayaan Intelektual Produk Pembelajaran Bagi Guru dan Calon Guru - Andriyani; Doni Susanto; Endang Wahyu Widayati; Fatimah Dwi Cahya; Yusuf Setyawan; Siti Khadijah (Forum Kerjasama Pendidikan Tinggi, 2024)
Intellectual property rights are private rights to works, ideas, and creativity of intellectual abilities that are protected by law. Teachers and prospective teachers as educators and academics have great potential to produce various innovative works during teaching and learning activities such as learning tools. The problem in the field is that many of these teachers' works have not been submitted for protection due to a lack of understanding of the technicalities of applying for IPR. Therefore, this service program aims to assist in the drafting of IPR for products that have been developed by teachers and prospective teachers. The method used includes procedures for exploring problems, conditions, and needs; analysis of situations, conditions, and identified problems; design of assistance evaluation instruments; implementation of assistance in drafting IPR applications; monitoring and discussion; evaluation and finally an activity report is prepared. The results of the analysis of the implementation of the mentoring show that there is effectiveness in the implementation of the mentoring that has been carried out both in terms of the criteria for understanding the material, presenting the material, and motivation. This is demonstrated by the achievement of a percentage or level of agreement of participants of more than 70% regarding the positive impact of this IPR application drafting assistance activity. With this mentoring activity, it is hoped that teachers' motivation to prioritize their teaching and learning on the development of potential IPR works can increase and cultural changes and positive perspectives towards documenting teachers' works with IPR can grow.